2019
DOI: 10.1007/s00259-019-04604-0
|View full text |Cite
|
Sign up to set email alerts
|

Individualized discrimination of tumor recurrence from radiation necrosis in glioma patients using an integrated radiomics-based model

Abstract: Purpose To develop and validate an integrated model for discriminating tumor recurrence from radiation necrosis in glioma patients. Methods Data from 160 pathologically confirmed glioma patients were analyzed. The diagnostic model was developed in a primary cohort (n = 112). Textural features were extracted from postoperative 18 F-fluorodeoxyglucose (18 F-FDG) positron emission tomography (PET), 11 C-methionine (11 C-MET) PET, and magnetic resonance images. The least absolute shrinkage and selection operator r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 45 publications
1
58
0
Order By: Relevance
“…Despite the promising performance of the developed radiomics model in the test dataset, further validation of the developed model in a large multicentric dataset is necessary. Since some studies have shown a synergistic effect by combining PET and MRI radiomics [ 24 , 72 ], the combination of FET PET radiomics with structural, as well as advanced, MRI radiomics should also be further investigated, especially in the light of the growing number of hybrid PET/MR scanners. This pilot study results are promising and suggest an important role for FET PET radiomics in neurooncology.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the promising performance of the developed radiomics model in the test dataset, further validation of the developed model in a large multicentric dataset is necessary. Since some studies have shown a synergistic effect by combining PET and MRI radiomics [ 24 , 72 ], the combination of FET PET radiomics with structural, as well as advanced, MRI radiomics should also be further investigated, especially in the light of the growing number of hybrid PET/MR scanners. This pilot study results are promising and suggest an important role for FET PET radiomics in neurooncology.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis: glioma [24] LASSO was suitable for a relatively small data set and could avoid overfitting with a L1 regularization term [24,34,56]. Genetic status: non-small cell lung cancer [34] Side effect: xerostomia [46] LASSO method used numerous iterations to link the non-zero contributory parameters to the chosen prognosis [64].…”
Section: Least Absolute Shrinkage and Selection Operator (Lasso)mentioning
confidence: 99%
“…Thus, the diagnostic efficiency was improved with the hybrid nomogram combing manual diagnosis. And, four radiomic features were extracted by LASSO method [24]. LASSO is suitable for a relatively small data set and can avoid overfitting.…”
Section: Least Absolute Shrinkage and Selection Operator (Lasso)mentioning
confidence: 99%
“…Wang et al used FDG PET, MET PET, and structural MRI images from 160 glioma patients for the development of a model to reliably diagnose tumor recurrence. 31 Before further processing, the patient cohort was divided into a training cohort ( n = 112) and a test cohort ( n = 48). The LASSO regression model was used for feature selection, and the model for predicting tumor recurrence was built using multivariable logistic regression analysis.…”
Section: Pet/mri Radiomics In Neuro-oncologymentioning
confidence: 99%